The Influence of Corporate Governance, and Corporate Social Responsibility Disclosure on Firm Value - Khusna, Meisya Maulida; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the Influence of Corporate Governance, Company Characteristics, and Corporate Social Responsibility Disclosure in Technology Sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The population in this study is technology sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. This study uses a purposive sampling technique, obtained from 10 companies so that the number of samples used is 40 observation data. The analysis used in this study is multiple linear regression analysis using SPSS version 25 as a calculation tool. Based on the results in this study, it shows that corporate governance, company characteristics, and corporate social responsibility disclosure have no effect on firm value.